Autologous fat transplantation alters gene expression patterns related to inflammation and hypoxia in the irradiated human breast. Issue 5 (25th February 2019) - Lindegren, A.; Schultz, I.; Sinha, I.; Cheung, L.; Khan, A. A.; Tekle, M.; Wickman, M.; Halle, M.
Abstract : Background: Radiation‐induced fibrosis, an adverse effect of breast cancer treatment, is associated with functional and cosmetic impairment as well as surgical complications. Clinical reports suggest improvement following autologous fat transplantation, but the mechanisms underlying this effect are unknown. A global gene expression analysis was undertaken to identify genetic pathways dysregulated by radiation and evaluate the impact of autologous fat transplantation on gene expression. Methods: Adipose tissue biopsies were taken synchronously from irradiated and contralateral non‐irradiated breasts, before and 1 year after autologous fat transplantation. Whole‐genome gene expression analyses were performed, and Hallmark gene set analysis used to explore the effect of radiotherapy and autologous fat transplantation on gene expression. Results: Forty microarrays were analysed, using bilateral biopsies taken from ten patients before and after autologous fat transplantation. Forty‐five pathways were identified among the 3000 most dysregulated transcripts after radiotherapy in irradiated compared with non‐irradiated breast ( P  ≤ 0·023; false discovery rate (FDR) no higher than 0·026). After autologous fat transplantation, 575 of the 3000 genes were again altered. Thirteen pathways ( P  ≤ 0·013; FDR 0·050 or less) were identified; the top two canonical pathways were interferon‐γ response and hypoxia. Correlative immunohistochemistry showed increased macrophage recruitment in irradiated tissues. Conclusion: The present findings contribute to understanding of how autologous fat transplantation can ameliorate radiation‐induced fibrosis. This further supports the use of autologous fat transplantation in the treatment of radiation‐induced fibrosis. Surgical relevance Clinical studies have indicated that autologous fat transplantation (AFT) stimulates regression of chronic inflammation and fibrosis caused by radiotherapy in skin and subcutaneous fat. However, there is a paucity of biological evidence and the underlying processes are poorly understood. Human data are scarce, whereas experimental studies have focused mainly either on the effect of irradiation or AFT alone. The present results indicate that radiotherapy causes dysregulated gene expression in fibrosis‐related pathways in adipose tissues in humans. They also show that AFT can cause a reversal of this, with several dysregulated genes returning to nearly normal expression levels. The study provides biological evidence for the impact of AFT on radiation‐induced dysregulated gene expression in humans. It supports the use of AFT in the treatment of radiation‐induced fibrosis, associated with severe morbidity and surgical challenges. Abstract : Effects on fibrosis after radiotherapy